Analysis on the causes that impact the availability of the plastic injection mold: a case study - Magalhães, Luiz Carlos dos Santos; Muniz, Fabiano Rodrigues; Azevedo, Andressa Amaral de (Brazilian Journal of Production Engineering, 2022)
The current case study had as its aim to analyze the main factors that affect the availability of plastic injection mold, which is part of the manufacturing process of headlights and lanterns at an automobile industry located in the state of Minas Gerais. To identify the mold with the most unavailability, the Pareto chart was used and, later, the causes of the problem and the analysis of failures were mapped. By a literature review, the concepts of maintenance and quality tools applied to this study were presented. It was found that the fixed Lantern Lens mold, model here called Alfa, presented the biggest number of interruptions in the production process for repair, due to the breakage of the tooling components. As a result, it was possible to identify improvements for the problem obtained and an action plan was then developed, suggesting to the managers the necessary action to eliminate the failure of the root cause of the problem. Attesting to the efficiency of the action plan, it is recommended to expand and standardize the model for the other tools in the search for continuous improvement of the stability of the process, focusing on obtaining better results.